InGaN-LD-pumped Pr3+:LiYF4 continuous-wave deep red lasers at 697.6 and 695.8 nm. (April 2015) - Xu, Bin; Cheng, Yongjie; Qu, Biao; Luo, Saiyu; Xu, Huiying; Cai, Zhiping; Camy, Patrice; Doualan, Jean-Louis; Moncorgé, Richard
Abstract: We report a power-scaled operation at π-polarized ~698 nm and σ-polarized ~696 nm deep red lasers in Pr:YLF crystal pumped by a 2-W InGaN LD (laser diode) after a pump beam reshaping. The maximum output power of the π-polarized laser emission at 697.6 nm was up to 348 mW with slope efficiency of about 32.7% in a free-running mode. The σ-polarized laser emission at 695.8 nm was also realized for the first time using a simple and compact Brewster-angle orientated intracavity etalon playing role as birefringence filter and the generated maximum output power of the 695.8 nm laser was up to 116 mW with slope efficiency of about 18.5% with respect to the absorbed pump power. Highlights: We obtain a π-polarized 698 nm laser in Pr:YLF crystal. We demonstrate the operation of a σ-polarized 696 nm laser in Pr:YLF crystal. Output power was scaled by using a 2-W beam reshaped InGaN laser diode. A Brewster-angle oriented glass etalon was used for birefringence filter. We measure the beam propagation factor M 2 of the 696 nm laser.